TRANSFORMASI DIGITAL DAN PENGUATAN KARAKTER PANCASILA DI SEKOLAH DASAR: STRATEGI ERA SOCIETY 5.0 - Erlita Ayu Nofridasari; Dian Hidayati (Jurnal Pendidikan Dasar, 2023)
The Society 5.0 era is impacting basic education, with significant changes in the way students learn through technology. Elementary schools have an important role in facing this digital transformation and strengthening the characters of Pancasila. Although technology enables access to online resources, challenges of disruption and uncertainty arise. This research details the strategy for integrating digital transformation with the formation of Pancasila character in elementary schools. Training teachers in the use of technology is important, while involving parents and the community is emphasized. This research uses a descriptive qualitative approach by collecting data through interviews and observations. The results of this research emphasize the importance of this integration to prepare a better generation in the Era of Society 5.0.